Being and becoming instrumental musicians and teachers: A post-qualitative exploration - Southcott, Jane; de Bruin, Leon R. (Frontiers in Education, 2022)
In trying to understand the complex interplay between effective learning and personal experience in instrumental music education we look to our own histories of becoming instrumental performers trained in conservatoires. We seek a a collective fusion of horizons of possibility to explore the relationships of musicians, both learners and teachers, with each other and their environments. We adopt the post-qualitative turn, as it offers space and place for simmering curiosities, introspections, evaluations, and yearnings. As pondering individuals, we question how we were pulled and prodded through the acquisition of instrumental expertise. We are a trumpeter and a clarinettist; we are performers. We are also music educators who both re-enact and resist what was given to us as gospel. We look beyond our ‘training’ to our becoming both musicians and pedagogues, a work that remains in progress. We offer this pathway to our students – how can we/they become the better music educator?